Ensayo uniforme de rendimiento de cinco (5) genotipos de ajonjolí (Sesamun indicum L) en Juan Guerra - Viena Saavedra, Edwar (1998)
The present experiment was conducted in the field owned by Mr. Cirilo Torres, Juan Guerra District - Bajo Mayo, Province and Department of San Martin In a period from 08/01/93 to 11/30/93. Geographically, 76 ° 21 'west longitude; 06 ° 31 'South and longitude 232 m.s.n.m; Sandy soil in a con un pH 6.4, 5.06 CaMg (meg / 100 gr) of soil, M.O (%) 1.6 clayey loam; 27.7 ppm P, K 0.4! ppm. The place was characterized by a dry tropical forest; with average monthly rainfall of 55.16 mm m / month 26.48 ° C. For statistical analysis Statistical randomized complete block design (BCR) with five treatments (4 cultivars plus 1 control) and Repetitions Four was used. The earliest fruiting Acarigua Genotype 42 days, and the smallest height to first capsule scammers 44.53 cm, length capsule Acarigua 4,18 cm scammers, swindlers and Inamar 3.05 cm, the most late to fruition genotypes Píritu inamar and 54 days and greater height to first capsule with a Piritu the 77.15 cm and smaller capsule length 2.83 cm. Numbers capsules per node without there much difference between the genotypes varying from 2 to 3 capsules per node. The mayor had Genotype Acarigua, number of seeds per capsule with seeds and 8.57 Criollo Reque Píritu with fewer seeds per seed capsule 7.52. Greater weight of 1000 seeds (g) Píritu son with 3,575 g 3,275 g Oil Enhanced with Reque witness and Creole with 3.22 g. The best yields were obtained with Píritu genotypes with 1824.7 kg / ha, Oil Enhanced with 1561.625 Kg / Ha. And Criollo Reque (control) with 1479.325 Kg / Ha. And under Performance Inamar genotypes with 1,049,325 kg / It ha and 975 kg / ha. Acarigua genotype. The economic analysis of the different genotypes indicates that all treatments exceeded production costs. Píritu gain genotype mayor was obtained with 23.60%, resulting in the Least Cost and Cost Mayor genotype resulted Acarigua with 45.0% Cost Ratio AS / Benefit percentage.